Predictive Factors of Keloid Formation in Congenital Foot Syndactyly - Sang Ho Oh, MD (Wolters Kluwer, 2021)
Background:. Keloid formation after syndactyly division is a stressful situation for patients. In our experience, digital enlargement may be involved in keloid formation following syndactyly divisions. Therefore, we aimed to identify predictive factors and reference values for keloid formation. Methods:. In this retrospective study, 11 keloid patients (seven children, four adults) and 11 nonkeloid patients after syndactyly division (control group) with the same sex, age, webspace division site, and operation were enrolled between 2008 and 2020. Using preoperative x-ray images, we compared bony width, length, area, and protruding index relative to the great toe between keloid and control groups. Additionally, reference values for keloid formation were obtained using receiver operating characteristic curves. Statistical analysis was performed using Spearman’s correlation test. Results:. When compared with the same digit in the normal foot, distal phalanx (P3) bony base width, area, and protruding index on keloid foot were significantly different between keloid group and control group. The reference values for keloid formation after syndactyly release were 1.34 for the P3 area ratio and 1.61 for the P3 triangular area ratio (using the horizontal length of the P3 base and P3 vertical length). The reliability of reference values for the P3 area ratio and P3 triangular area ratio was excellent for all patients. Conclusions:. If digital enlargement in distal phalanx is present when compared with adjacent toe in patients who had undergone primary foot syndactyly divisions, risk of keloid development should be communicated preoperatively, and preventive strategies for keloid development and close observations are required.